Reproductive health and rights in East Jerusalem: the effects of militarisation and biopolitics on the experiences of pregnancy and birth of Palestinians living in the Kufr 'Aqab neighbourhood. (27th October 2017) - Hamayel, Layaly; Hammoudeh, Doaa; Welchman, Lynn
Abstract: Research with marginalised communities points to the need to understand political determinants of reproductive health. For residents of Kufr 'Aqab neighbourhood, Israeli biopolitics in East Jerusalem can be barriers to access to maternal health. This is manifested in women having to cross military checkpoints to give birth in hospitals located in Jerusalem to make their children eligible for "permanent residency", a document required for Palestinians to live in Jerusalem. A basic qualitative design is utilised, and semi-structured in-depth interviews with 27 women and 20 men were conducted and thematic analysis was used to extract themes and subthemes. Women reported exposure to risky conditions during pregnancy and worries of giving birth at checkpoints. Social support was restricted for some women due to inability of the husband/family to reach the hospital at the time of birth. Men reported distress related to inability to attend birth. Giving birth in a Jerusalem hospital, as part of passing residency to children, was perceived as reaffirming Palestinian presence in the City and transforming sites of suffering to sites of resistance. Israeli residency policies and segregation of Jerusalem affect Kufr 'Aqab residents' pregnancy and birth on physical, social and psychological levels. Results indicate the importance of incorporating political determinants of access to maternal care and safe pregnancy in the conceptualisation of reproductive rights.